Effects of plant-derived anti-leukemic drugs on individualized leukemic cell population profiles in Egyptian patients - ABOUL-SOUD, MOURAD A. M. (D.A. Spandidos, 2016)
Leukemias are a group of cancer types that originate from blood-forming tissues. In this disease, an abnormally large number of immature white blood cells is produced by the bone marrow. The relationship between treatments with plant-derived drugs and leukemia-associated immunophenotypes (LAIPs) of clinically isolated leukemia cells has yet to be established. The aim of the present study was to develop a preliminary clinical prognostic map for commonly expressed LAIPs in patients clinically diagnosed with leukemia, as well as to assess the potential involvement of LAIPs in the response rate to 10 natural products of plant origin. An increased expression of LAIPs, including CD4, CD14, CD33 and CD34, was considered a surrogate marker of the desired response of leukemia cells to treatment with plant-derived drugs. By contrast, the increased expression of the LAIPs, MPO and DR, was associated with poor prognostic outcomes following treatment with the plant-derived drugs. The results showed that 5 of the 10 plant-derived drugs tested induced the expression of several desirable LAIPs biomarkers. These findings clearly highlight the potential treatment efficacy of certain plant-derived drugs against leukemic cell types.